IDENTIFIKASI BIOKIMIA DAN AKTIVITAS ANTIBAKTERI ISOLAT BAKTERI ASAM LAKTAT DARI LIMBAH SAYUR SAWI (Brassica juncea L.) - Sukriani Kursia; Imrawati Imrawati; Aliansyah Halim; Sasmita Sasmita; Fildzah Hanifah (Universitas Islam Negeri Alauddin Makassar, 2019)
Lactic Acid Bacteria (LAB) is a group of bacteria that produce lactic acid as the main product in carbohydrate fermentation. LAB has a major role to fight against pathogenic bacteria through peptide compounds. LAB can be found in vegetables that contain carbohydrates. The research objective was to determine biochemically and determine the antibacterial activity of LAB isolates from Brassica juncea L vegetable waste. Biochemical testing methods include TSIA, Indol, MR_VP, motility, temperature resistance and salt resistance tests. While testing the activity using the disc diffution method is used by the media Mueller Hinton Agar against Basillus subtilis, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus mutans, Salmonella thypimurium, and Propionibacterium acnes. Preparation of the test sample was carried out by inoculating LAB isolate stock for 1x24 hours at 37 ° C. Biochemical identification results showed that LAB isolates were able to ferment glucose, negative in indole and VP testing, positive in MR testing was characterized by obtaining acidic pH, non-motile nature, living at 37 ° C, and resistant to several salt concentrations (5-10%). The results of testing antibacterial activity based on univariate analysis showed differences in the activity of each of the test bacteria obtained p = 0,730 (p>0,05). LSD analysis showed no significant differences between all isolates. Conclusion: isolates obtained included LAB group from the family Lactobacillaceae, genus Lactobacillus sp and the antibacterial activity was broad spectrum